Audience Design and Oral Exegesis: Interpreting the Hadith of Secret Charity on YouTube - Ramadhani, Rikana Nur (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2025)
The study of hadith in digital spaces reveals the emergence of diverse forms of oral exegesis on the hadith concerning secret charity—when the left hand does not know what the right hand gives. This research focuses on two questions: how is the oral exegesis of this hadith presented on YouTube, and how does audience design shape its form? A qualitative method with the theoretical framework of audience design was employed to analyze five lecture videos of popular preachers. The findings show variations in delivery: Gus Mus and KH. Marzuqi Mustamar uses a relaxed style with themes of exemplary scholars for audiences of students and rural communities; Ustadz Abdul Somad emphasizes stories of the Companions for a direct digital audience; while Ustadz Firanda Andirja and Ustadz Syafiq Riza Basalamah highlight scriptural proofs and warnings against riya for urban congregations. These findings affirm that audience design influences the form of oral exegesis, yet the substance of the hadith remains preserved. The contribution of this study is to demonstrate that oral exegesis represents a creative adaptation in conveying hadith through da’wah.